PELATIHAN KEPEMIMPINAN PADA ORGANISASI SISWA INTRA SEKOLAH (OSIS) MADRASAH ALIYAH SE-KABUPATEN LAMPUNG TIMUR - Kagungan, Dian; Yulianto, Yulianto; Sulistiowati, Rahayu; Caturiani, Susana Indriyati (Prosiding Pengabdian FISIP Unila, 2012)
The courses of training based on fundamental leadership concepts that said leadership is activity or exertion to influence people to obtain the group goal voluntarily. Because of that, a leader needs knowledge and skill in communication and also motivation. Communication, in brief, means process of sending and aceppting message from someone to other (s). Motivation is efforts  that cause a person or people does/do certain thing that she/he/they wants/want to do. Nowadays, leader is meant as a servant not a boss. She/he should serves everyone in organization, include their subordinates.  This training was run on Tuesday,  17 July  2012 at  Madrasah Aliyah Negeri 1, Batanghari,  Lampung Timur. The participant number 35 students, concist of 16 girls  and 19 boys. The method of training are giving a lectures and games. The result that is reached by the participants, is raising in cognitive aspects. The lowest is 15 % and the highest is 50 %.   The conclusion of this leadership training for board of OSIS are first, generaly they joined this activity enthusiasticly and were motivated to implement this courses in their organization. Second, the average of cognitive improvement is 29,09 %. Base on this experience, there are two suggestions, firstly, it is necessary to continue leadership training for board of OSIS both of senior high school and yunior high school. Secondly, the operation of training can cooperate to universities.  Key words : Leade rship, Ability, Board of OSIS